Peran Pelatihan SDM dan Locus of Control terhadap Kepuasan Kerja dan Implikasinya terhadap Produktivitas Kerja Aparatur Desa di Kabupaten Lebak - Susanto, Rois; Rustandi, Tata; Suadma, Udin (J-MAS (Jurnal Manajemen dan Sains), 2024)
In order to effectively navigate the changing landscape of modern work, it is crucial for human resources to possess dependable, autonomous, and proficient skills in carrying out their primary responsibilities and functions as employees. This includes demonstrating a strong commitment and a strong work ethic that aligns with their job requirements, ultimately leading to optimal work productivity. Work productivity is a cognitive disposition that consistently enhances existing conditions. An enhanced conviction in one's ability to perform a task more effectively than previously. The objective of this study is to assess and examine the impact of HR training, locus of control, and job satisfaction on work productivity, as well as the impact of HR training and locus of control on job satisfaction. This study employs a quantitative descriptive research methodology. The descriptive approach in research seeks to quantify and measure existent phenomena. Quantitative data analysis is employed to compute the statistical outcomes of Structural Equation Modeling-Partial Least Square (SEM-PLS) with the objective of testing the hypothesis. The hypothesis test results indicate that HR training does not have a substantial impact on work productivity. However, Locus of Control has a notable beneficial influence on work productivity and job satisfaction. HR training does not have any impact on job satisfaction, while Locus of Control has a notable positive influence on job satisfaction. Additionally, it is seen that work productivity is significantly improved by HR training. The findings indicate that HR training does not have a discernible impact on productivity and work satisfaction. Work productivity is significantly enhanced by job happiness. The impact of Locus of Control on the productivity and job satisfaction of Village Officials in Lebak Regency is notably good.